Plan de práctica académica-profesional en centro de atención psicológica CAPSI (2011)
This paper aims to show the practical-theoretical IPS made to theservice provider CAPSI - psychologically Care Center at the Catholic University of Pereira, designed by collecting andanalyzing information, developing needs assessment and thenthe construction of three (3) axes of clinical, educational and organizational psycho-which are raised and directed towards realizing this practice exercise, the same way we present the results and / or presented difficulties when implementing and running priorities for assistance within the institution. In addition to the conclusions and recommendations given by the practitioner of psychology.